Association of microbiota polyphenols with cardiovascular health in the context of a Mediterranean diet. (March 2023) - Domínguez-López, Inés; Arancibia-Riveros, Camila; Marhuenda-Muñoz, María; Tresserra-Rimbau, Anna; Toledo, Estefanía; Fitó, Montserrat; Ros, Emilio; Estruch, Ramon; Lamuela-Raventós, Rosa M.
Graphical abstract: Highlights: A score of microbial phenolic metabolites was associated with higher adherence to the Mediterranean diet. Polyphenols derived from the gut microbiota were related to a better cardiovascular health status. Urolithin B glucuronide was associated with lower concentrations of LDL-cholesterol. Abstract: Background and aims: The Mediterranean diet (MedDiet) is rich in polyphenols, phytochemicals that are beneficial for cardiovascular health. Phenolic compounds have poor bioavailability but they are extensively metabolized by the gut microbiota. Therefore, we aimed to assess the association of microbial phenolic metabolites (MPM) with adherence to the MedDiet, and their relationship with ideal cardiovascular health (ICVH) and cardiovascular risk factors. Methods and results: This cross-sectional substudy within the PREDIMED trial included 200 participants from the Barcelona-Clinic recruitment center. Five MPM were identified and quantified using a novel method based on liquid chromatography coupled to mass spectrometry: protocatechuic acid (PCA), enterodiol glucuronide (EDG), enterolactone glucuronide (ELG), vanillic acid glucuronide (VAG) and urolithin B glucuronide (UBG). Multivariable-adjusted regressions were used to evaluate the associations between MPM and MedDiet adherence, ICVH score, biochemical parameters, and blood pressure. Additionally, an MPM score was calculated as the weighted sum of MedDiet adherence and ICVH and found to be directly associated. Among individual polyphenols, UBG was inversely associated with LDL-cholesterol. Conclusions: A score of urinary MPM was associated with higher adherence to the MedDiet and ICVH, and individual MPM were related to better cardiovascular health. These findings suggest that the MedDiet may affect gut microbiota, whose metabolites are linked with cardiovascular health.